Low dietary diversity is associated with linear growth faltering and subsequent adverse child developmental outcomes in rural Democratic Republic of the Congo (REDUCE program). Issue 3 (21st March 2022) - George, Christine Marie; Coglianese, Nicole; Bauler, Sarah; Perin, Jamie; Kuhl, Jennifer; Williams, Camille; Kang, Yunhee; Thomas, Elizabeth D.; François, Ruthly; Ng, Angela; Presence, Amani S.; Jean Claude, Bisimwa R.; et al.
Abstract: The objective of this study was to investigate the association between dietary diversity, child growth and child developmental outcomes. This was a prospective cohort study. Developmental outcomes were assessed by communication, fine motor, gross motor, personal social, problem solving and combined developmental scores measured by the Extended Ages and Stages Questionnaire (EASQ) at a 6‐month follow‐up visit. Height and weight were measured at baseline and a 6‐month follow‐up. Baseline minimum dietary diversity (MDD) for children 6–23 months old was defined by consumption of five or more of the following food groups: (1) breast milk; (2) grains, roots and tubers; (3) legumes and nuts; (4) dairy products; (5) flesh foods; (6) eggs; (7) vitamin A‐rich fruits and vegetables and (8) other fruits and vegetables. Participants were 117 children 6–23 months of age. Linear growth faltering was defined as a significant decline ( p  < 0.05) in length‐for‐age Z ‐scores (LAZ) between baseline and follow‐up. Regression models were performed. The study was conducted in rural eastern Democratic Republic of the Congo (DRC). MDD was positively associated with change in LAZ (coefficient: 0.87 [95% confidence interval [CI]: 0.33, 1.40]), and a reduced odds of stunting (LAZ < −2) (odds ratio: 0.21 [95% CI: 0.07, 0.61]). MDD was also associated with a significantly higher combined EASQ‐ Z ‐scores (coefficient: 0.34 [95% CI: 0.003, 0.68], higher communication EASQ‐ Z ‐scores [0.50 {95% CI: 0.14, 0.85}], and higher personal social EASQ‐Z‐scores [0.46 {95% CI: 0.11, 0.82}]). This study provides further evidence demonstrating the need for interventions to improve dietary diversity among young children. Key messages: Dietary diversity was low among young children in our study setting in rural eastern Democratic Republic of the Congo. Low dietary diversity was associated with linear growth faltering and lower child developmental outcomes. This study provides further evidence demonstrating the need for interventions to improve dietary diversity among young children to improve child health.